The ASAS-SN catalogue of variable stars – V. Variables in the Southern hemisphere. Issue 1 (30th September 2019) - Jayasinghe, T; Stanek, K Z; Kochanek, C S; Shappee, B J; Holoien, T W-S; Thompson, T A; Prieto, J L; Dong, S; Pawlak, M; Pejcha, O; Shields, J V; Pojmanski, G; et al.
ABSTRACT: The All-Sky Automated Survey for Supernovae (ASAS-SN) provides long baseline (∼4 yr) light curves for sources brighter than V ≲ 17 mag across the whole sky. As part of our effort to characterize the variability of all the stellar sources visible in ASAS-SN, we have produced ∼30.1 million V -band light curves for sources in the Southern hemisphere using the APASS DR9 (AAVSO Photometric All-Sky Survey Data Release) catalogue as our input source list. We have systematically searched these sources for variability using a pipeline based on random forest classifiers. We have identified ${\sim } 220\, 000$ variables, including ${\sim } 88\, 300$ new discoveries. In particular, we have discovered ${\sim }48\, 000$ red pulsating variables, ${\sim }23\, 000$ eclipsing binaries, ∼2200 δ-Scuti variables, and ${\sim }10\, 200$ rotational variables. The light curves and characteristics of the variables are all available through the ASAS-SN variable stars data base (https://asas-sn.osu.edu/variables ). The pre-computed ASAS-SN V -band light curves for all the ∼30.1 million sources are available through the ASAS-SN photometry data base (https://asas-sn.osu.edu/photometry ). This effort will be extended to provide ASAS-SN light curves for sources in the Northern hemisphere and for V  ≲ 17 mag sources across the whole sky that are not included in APASS DR9.